Dear Comrade President: Oliver Tambo and the foundations of South Africa's constitution - Budlender, Debbie (New Agenda: South African Journal of Social and Economic Policy, 2024)
At 372 pages of main text, and about 70 further pages of appendices, notes and index, this book is densely packed with information. It is also packed with characters, events and developments that are relatively well known together with others that will be new to many readers. The book bears the stamp of its dedicated author, but the stamp of Albie Sachs, credited on the cover and in the text for “editorial contributions”, is also evident. Indeed, Albie makes regular appearances in the story-line, which spans several continents and decades, from beginning to end. It is for this very reason that Odendaal decided he should not be a co-author.